Spectrophotometric determination of acyclovir after its reaction with ninhydrin and ascorbic acid - Ukpe Ajima, Johnson Ogoda Onah (Journal of Applied Pharmaceutical Science, 2015)
Acyclovir is a purine-based nucleoside antiviral agent used in the management of Herpes simplex and other viral infections. The present study is aimed at developing and validating a simple and rapid spectrophotometric method for its determination. The mechanism of the proposed method is based on the condensation/coupling reaction between Acyclovir and Ninhydrin-Ascorbic acid at pH 5. A purple colored product with maximum absorption at 540 nm was assayed to quantitatively evaluate the drug content in the formulation. The calibration curve was found to be linear up to 30 µg/ml. Analyte recovery tests carried out by the proposed method gave recovery of between 96.9 – 102.0%. Molar absorptivity and Sandells’ sensitivity were determined to be 41,071.43 L mol-1 cm-1 and 1.84 µg cm-2 respectively. The precision was assessed by determining the inter-day and intra-day variation which ranged between 1.45 – 1.63 % and 0.81 – 1.12 % respectively. The results show that the reaction produced a stable product and the proposed method is cost-effective and possesses adequate accuracy, precision and sensitivity. It can therefore be conveniently applied for the determination of acyclovir in dosage forms.
Keywords: Acyclovir, Ninhydrin, Ascorbic acid, Spectrophotometry, Pharmaceutical analysis.